EFFECT OF CURCUMA LONGA EXTRACT ON BIOFILM FORMATION BY STREPTOCOCCUS MUTANS - G, Gokul; Rv, Geetha (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: To find the effect of Curcuma longa extract on biofilm formation by Streptococcus mutans. Methods: The organism S. mutans was isolated from saliva sample using special media (Mutans - sanguis agar) and maintained in tryptone soya agar at 4Â°C in Department of Microbiology, Saveetha Dental College and Hospitals. Results: From the study, we infer that 78.35% of inhibition of the biofilm formation is seen with 100 ug of curcumin extract. From the result, it is evident that curcumin has a very good inhibitory effect on S. mutans growth. Conclusion: The study concludes the inhibitory action of curcumin on S. mutans by preventing biofilm formation.